Involvement of mitogen-activated protein kinase signaling pathways in microcystin-LR-induced apoptosis after its selective uptake mediated by OATP1B1 and OATP1B3 - Komatsu, Masaharu; Keppler, Dietrich (Toxicological sciences, 2007)
Abstract. The serine/threonine protein phosphatase (PP) 2A inhibitor, microcystin-LR, selectively induces liver damage and promotes hepatocarcinogenesis. It is thought that microcystin-LR affects hepatocellular viability mainly through inhibition of PP2A, partially through PP1, and, in addition, by generation of reactive oxygen species (ROS).